Spectral characteristics of Pr3+-doped lead phosphate glasses for optical display device and gain media applications - Ch. Basavapoornima; T. Maheswari; C. R. Kesavulu; W. Pecharapa; J. Kaewkhao; C. K. Jayasankar (My University, 2020)
The present work is concentrated on spectral analysis of Pr3+-doped lead phosphate (PPbKANPr) glasses for visible lasers and optical amplifier applications where the PPbKANPr glasses were prepared by a melt quenching technique. Based on the absorption spectrum and the well-known Judd-Ofelt (JO) theory, the JO intensity parameters were determined and then used to calculate the various radiative parameters for higher excited luminescent states of Pr3+ ion. The derived JO parameters (× 10−20 cm2) were found to be Ω2 = 1.51, Ω4 = 18.03 and Ω6 = 19.81. The luminescence spectra exhibit emission bands in the visible region of 480-780 nm and with the increasing of Pr3+ ion concentration, the emission intensities were decreased due to concentration quenching. The analysis of the results confirms that the PPbKANPr glasses are useful for visible lasers as well as optical amplifiers.
Keywords: Phosphate glass; Visible spectrum; Glass properties and applications